Patients Compliance In Limiting Liquid Intake And Nutrition Can Regulate Biological And Biochemical Value Of Blood In Patients Through Hemodialysis - Achmad Fauzi; Rusmai Triaswati; Jumari Jumari (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: IDWG (Intradialytic Weight Gain) is one of the indicators to evaluate the biological value of weight change between the time of dialysis whose value is influenced by patient adherence to limit the intake of fluids and foods high in sodium, while potassium, sodium, albumin, urea and creatinine is an indicator of blood biochemical values whose value is influenced by patient adherence to limit the intake of nutrients. Objectives: Hospital hemodialysis unit Bekasi Methods: The sample was selected using the technique of Non-Probability Sampling or non-random sampling with purposive sampling method, and came up with 73 respondents. Results: Data collection was done through two types of data namely primary and secondary data. Primary data obtained from the questionnaires A and B by the respondent directly and secondary data obtained from the results of direct measurements by researchers that IDWG and blood biochemistry values obtained from the patient laboratory results. The results showed a significant relationship between the level of compliance yng patients for limiting the intake of fluids and nutrients to the IDWG, potassium, sodium, albumin, urea and creatinine with P Value successively ie, p = 0.0005; p = 0.020; p = 0.008; p = 0.013; p = 0.002; p = 0.004 with a = 0.05. Conclusion: of this study can be used in planning interventions appropriate education, in order to prevent and decrease the physical deterioration of the condition of patients on dialysis due to less or no maximum to limit fluid intake and nutrition.